Origin of Mg-rich clay minerals in the first member of Maokou Formation in the middle Permian in the Central and Southern Sichuan Basin (China) and their implications on supergene and hypogene fluid regimes - Wancang Tan; Xiandong Wang; Pengfei Niu; Xueying Jin; Liang Zhao; Ying Wang; Yaguang Li; Yu Zhang (PLoS ONE, 2025)
The first member of Maokou Formation (MF1) in the Sichuan Basin is characterized by marl strata that serve as effective natural gas reservoirs. Notably, the development of MCMs (magnesium-rich clay minerals) plays a significant role in enhancing these reservoirs, especially sepiolite and talc. The diagenesis of sepiolite in the MF1 (Middle Permian) of the central and southern Sichuan Basin was investigated through core and thin section observations, combined with X-ray diffraction (XRD), scanning electron microscopy (SEM), whole-rock major and trace element analysis, and LA-ICP-MS elemental analysis. MCMs occur in various forms, including lamellae, lens-like structures, clastic, strip-like, and metasomatic bioclasts. The MCMs appear gray-black on core samples, with XRD analysis indicating sepiolite and talc as the primary constituents. Under scanning electron microscope, these MCMs are typically observed as granular particles dispersed alongside quartz, while some replace bioclasts in a concentric zonal pattern. Based on rare earth element (REE) characteristics, MCMs can be classified into two genetic categories: sedimentary and hydrothermal types. Sedimentary MCMs exhibit a negative δEu anomaly, high Al/(Al + Fe + Mn) and Y/Ho ratios, and lack heavy REE enrichment. In contrast, hydrothermal MCMs display the opposite characteristics, positive δEu anomaly, low Al/(Al + Fe + Mn) ratio, and elevated concentrations of hydrothermal-related elements. Sedimentary MCMs form through chemical precipitation or metasomatic processes in silicon- and magnesium-rich seawater, while hydrothermal MCMs result from siliceous hydrothermal activity affecting magnesia-rich carbonate rocks. The diagenetic evolution of MCMs contributes to the formation of unconventional reservoirs in MF1 strata by creating organic and clay shrinkage pores. Thus, MCMs-enriched marl represents a promising target for oil and gas exploration within MF1 strata in the Sichuan Basin.